Scrotal thermography and doppler ultrasonography of the testicular artery of buffaloes subjected to environmental heat stress - Neto, Carlos Ramires [UNESP]; de Resende, Hélène Lacerda [UNESP]; Monteiro, Gabriel A. [UNESP]; Zorzetto, Mariana F. [UNESP]; da Silva, Yamê F. R. Sancler [UNESP]; Oba, Eunice [UNESP] (My University, 2013)
The process of spermatic division and differentiation (spermatogenesis) occurs with intratesticular temperature lower that the corporal temperature and for that is essential that the testicular thermoregulation mechanism occurs properly. For evaluation of the scrotal surface temperature can be used the infrared thermography or testicular sensors, besides that, can be evaluated the blood flux in the spermatic cord through the Doppler ultrasonography. Therefore the objective of this study was the evaluation of the scrotal thermography and Doppler flowmetry of the testicular artery of buffaloes subjected to environmental heat stress. For that were used seven healthy buffaloes, with age of 3 and 4 years, of the Murrah breed. For the surface scrotal temperature measurement (SST, °C) and superficial neck temperature (SNT, °C) was used the infrared termography (Infra CamTM™ of the brand FLIR Systems Inc.), then Doppler flowmetry of the testicular artery in the region of the spermatic cord through the ultrasonography (Mylab 5, Esaote®) and measurement of the rectal temperature (RT, °C). The evaluations were done in two moments: moment 1 (M1) with all the animals in the shade (Temperature=32,2°C) and moment 2 (M2) after 3 hours of exposure of animals to the sun (Temperature=38,7°C To calculate the resistivity index (RI) and pulsatility index (PI), spectra were obtained from pulsed Doppler in three random regions of the testicular artery in the spermatic cord. Data were subjected to analysis of variance (ANOVA) followed by T test, using a significance level of 5%. There was an increase (p<0,05) of RT (37,4±0,4a vs 39,0±0,3b; M1 and M2 respectively), SST (30,6±1,4a vs 35,2,0±1,0b; M1 and M2 respectively) and SNT (33,1±2,5a vs 38,5,0±0,3b; M1 e M2 respectively) e RI (0,67±0,1a vs 0,74±0,1b; M1 e M2 respectively) in M2. Increasing trend was observed (0,05>p>0,01) in PI (1,10±0,4a vs 1,23±0,2b; M1 and M2 respectively) in M2. The results of the present study allow us to conclude the healthy buffaloes have the scrotal average surface temperature 3°C lower that the body temperature and that the exposure of 3 hours to sun in healthy buffaloes causes thermal stress to the animals and changes in its surface scrotal temperature, and the Doppler flowmetry of the testicular artery demonstrating the importance of thermal management for breeding buffaloes. Besides that, the thermography and the Doppler ultrasonography presented great potential to detect changes of testicular perfusion, being a promising additional test in the buffalo andrological evaluation.
Keywords: Buffalo; Doppler ultrasonography; Testicular thermoregulation; Thermal stress; Thermography